2011
DOI: 10.1007/s13197-011-0297-0
|View full text |Cite
|
Sign up to set email alerts
|

Quality evaluation of millet-soy blended extrudates formulated through linear programming

Abstract: Whole pearl millet, finger millet and decorticated soy bean blended (millet soy) extrudates formulations were designed using a linear programming (LP) model to minimize the total cost of the finished product. LP formulated composite flour was extruded through twin screw food extruder at different feed rate (6.5-13.5 kg/h), screw speed (200-350 rpm, constant feed moisture (14% wb), barrel temperature (120°C) and cutter speed (15 rpm). The physical, functional, textural and pasting characteristics of extrudates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 31 publications
(28 reference statements)
1
25
0
Order By: Relevance
“…A similar result in PV was obtained in pearl millet based extrudates after the addition of WPC (Yadav et al, ). Balasubramanian, Singh, Patil, and Onkar () reported the decreasing trend of viscosity parameters with increased legume levels. Table shows the significant effect of VCO cake ( p < 0.001) on PV.…”
Section: Resultsmentioning
confidence: 95%
“…A similar result in PV was obtained in pearl millet based extrudates after the addition of WPC (Yadav et al, ). Balasubramanian, Singh, Patil, and Onkar () reported the decreasing trend of viscosity parameters with increased legume levels. Table shows the significant effect of VCO cake ( p < 0.001) on PV.…”
Section: Resultsmentioning
confidence: 95%
“…Bhattacharya [18] had reported that the expansion of extruded product is dependent on the degree of gelatinization. Balasubramanian et al [19] reported positive effect of moisture content on expansion because starch gelatinization dependent on the available feed moisture. Expansion ratio with respect to variations in barrel temperature followed almost increasing trend with maximum values for 140°C barrel temperature and minimum values at 120°C barrel temperature.…”
Section: Expansion Ratiomentioning
confidence: 99%
“…As shown in Table 6 at the optimal condition feed moisture, blend ratio and barrel temperature was found to be 25%, 5:95 and 140°C, respectively. Balasubramanian et al [19] had reported better physico chemical properties for millet based extrudates developed at 120°C having 14% moisture content.…”
Section: Bulk Densitymentioning
confidence: 99%
“…During formulation of a product, computer‐based modeling gives features to reduce error and biases (Ghosh, ). To formulate the product at the best constraints are set on feed ingredients, thereafter objective function has to be defined to achieve the desired goal (Balasubramanian et al, ; Gupta, Chandan, & Singh, ; Kowalski, Li, & Ganjyal, ). CCRD has been widely used for experimental design to generate a standard optimized solution (Capanzana & Buckle, ) due to its high efficiency.…”
Section: Introductionmentioning
confidence: 99%